Epigenetic landscape of pancreatic neuroendocrine tumours reveals distinct cells of origin and means of tumour progression - Di Domenico, Annunziata; Pipinikas, Christodoulos P.; Maire, Renaud S.; Bräutigam, Konstantin; Simillion, Cedric; Dettmer, Matthias S.; Vassella, Erik; Thirlwell, Chrissie; Perren, Aurel; Marinoni, Ilaria (Communications biology, 2020)
Recent data suggest that Pancreatic Neuroendocrine Tumours (PanNETs) originate from α- or β-cells of the islets of Langerhans. The majority of PanNETs are non-functional and do not express cell-type specific hormones. In the current study we examine whether tumour DNA methylation (DNAme) profiling combined with genomic data is able to identify cell of origin and to reveal pathways involved in PanNET progression. We analyse genome-wide DNAme data of 125 PanNETs and sorted α- and β-cells. To confirm cell identity, we investigate ARX and PDX1 expression. Based on epigenetic similarities, PanNETs cluster in α-like, β-like and intermediate tumours. The epigenetic similarity to α-cells progressively decreases in the intermediate tumours, which present unclear differentiation. Specific transcription factor methylation and expression vary in the respective α/β-tumour groups. Depending on DNAme similarity to α/β-cells, PanNETs have different mutational spectra, stage of the disease and prognosis, indicating potential means of PanNET progression. Di Domenico et al., provide a comprehensive assessment of DNA methylation in a large cohort of pancreatic neuroendocrine tumors. This work provides new insights into the epigenetic heterogeneity of the disease and cellular basis.